Tranzycja uczniów z niepełnosprawnością intelektualną z edukacji na rynek pracy - perspektywa rodzica - Otrębski, Wojciech; Mariańczyk, Katarzyna (Interdyscyplinarne Konteksty Pedagogiki Specjalnej, 2018)
The interactive model of vocational rehabilitation includes two key components: the rehabilitated individual and the vocational rehabilitation environment. The interaction of these two elements should contribute to the improvement of vocational competencies of people with disabilities[1]. Due to the fact that parents are considered as the second main contributors (just after teaching staff) of vocational training as well as life and vocational orientation of children and teenagers[2], the family environment can be treated as a significant part of the vocational rehabilitation of people with intellectual disability. Therefore, the aim of this study was to discover how parents of individuals with intellectual disability participate, if they do, in vocational training of their children. Materials and Methods: The study was conducted among parents of special vocational schools graduates using the survey ASZ-S-R by W. Otrębski and K. Mariańczyk. The results are based on the answers of 71 parents/guardians of graduates of special vocational schools located in South-East part of Poland. Results: Nearly 88% of respondents declared that they supported the vocational preparation of their children by holding talks about various vocational activities. Circa 40% of them also provided help to their children with disabilities to find employment (e.g. by searching for job advertisements); nevertheless, over a quarter do not engage in such an activity at all. Active participation of parents of graduates with intellectual disability is necessary to prepare their children to undertake vocational activities. [1] W. Otrębski, Interakcyjny model rehabilitacji osób z upośledzeniem umysłowym, Wydawnictwo KUL, Lublin, 2007, s. 56. [2] J. Stankaitytė, N. Janonytė, J. Muriniene, A. Paszkowska-Rogacz, Etapy rozwoju dziecka i wyboru kariery zawodowej, [w:] Moje dziecko wybiera karierę zawodową, red. A. Paszkowska-Rogacz, Społeczna Wyższa Szkoła Przedsiębiorczości, Łódź, 2008, s. 19-33.